An Experimental Study on the Mechanical Properties of High-Temperature Granite under Natural Cooling and Water Cooling - Yanan Gao; Yunlong Wang; Taiping Lu; Liuzhou Li; Jinwen Wu; Zetian Zhang (Advances in Materials Science and Engineering)
With the further development of deep rock mechanics engineering, such as the exploitation and utilization of geothermal resources, the exploitation of deep mineral resources, and the safe disposal of nuclear waste, the study of mechanical properties of deep high-temperature rock is gaining the attention of the researchers. However, not only the high temperature but also the cooling condition/method that will be used in the construction such as drilling cooling will also greatly affect the mechanical properties of the rock. In this paper, the mechanical behaviour and the evolution of the mechanical properties of the high-temperature (600°C–1,000°C) granite under different cooling methods are studied. The following conclusions can be obtained: (1) The peak stress of the granite decreases with the heating temperature. Compared with natural cooling, water cooling has a more significant effect on strength degradation. (2) The increase of the heating temperature increases the maximum axial strain of the granite. The water cooling method more greatly induces the maximum axial strain of granite than the natural cooling. The maximum axial strain of the specimen under the water cooling reaches 117.3% of that under natural cooling (800°C). (3) The elastic modulus of the granite decreases with the heating temperature. Water cooling will have a stronger effect on the reduction of the elastic modulus than natural cooling. The maximum difference value (2.02 GPa) of the elastic modulus under the different cooling methods occurs at the temperature of 800°C. (4) Poisson’s ratio of the granite increases with heating temperature, and the cooling method does not have an evident effect on it. The relationship between Poisson’s ratio and the heating temperature under different cooling methods can be described using the linear model. (5) According to the influence of the temperature on the peak stress, the elastic modulus, and Poisson’s ratio, the heating temperature domain can be divided into the unapparent zone, the significant zone, and the mitigation zone. (6) The thermal stress due to the nonuniform temperature field and the different thermal expansion coefficients is incompatible. Such incompatibility stresses the essences of the degradation of the mechanical properties of the granite.